Poorly Differentiated Ovarian Sertoli-Leydig Cell Tumor in a 16-Year-Old Single Woman: A Case Report and Literature Review - Ahmed Abu-Zaid; Ayman Azzam; Lama Abdulhamid Alghuneim; Mona Tarek Metawee; Tarek Amin; Turki Omar Al-Hussain (Hindawi Limited, 2013)
Sertoli-Leydig cell tumor (SLCT) of ovary is an exceedingly unusual neoplasm that belongs to a group of sex cord-stromal tumors of ovary and accounts for less than 0.5% of all primary ovarian neoplasms. Very few case reports have been documented in the literature so far. Herein, we report a case of primary poorly differentiated ovarian Sertoli-Leydig cell tumor (SLCT) involving the left ovary in a 16-year-old single woman who presented with a 3-month history of a pelviabdominal mass, acne, hirsutism, and menstrual irregularities. In addition, a literature review on ovarian SLCTs is provided.